Eddie Winston is looking for love : [large type] a novel - Cronin, Marianne (Thorndike Press large print top shelf., 2025)
"Eddie Winston is 90 years old. He has lived and he has loved, but he has never been kissed. A true gentleman and incurable romantic, Eddie spends his days volunteering at a charity shop, where he sorts through the donations, preserving letters and tokens of love along the way. And it is here that he meets Bella, a troubled young woman who, at 24 years old, has just lost the love of her life. When Bella learns that Eddie is yet to have his first kiss, she resolves to help Eddie Winston finally find love, sparking an adventure that will take them to unexpected places and, they hope, bring Eddie Winston to the moment he has waited for all his life"--